Pengaruh Variabel Demografi dan Technology Readiness Terhadap Perilaku Belanja Online di Kota Denpasar - Andika, I Wayan Ardy; Rastini, Ni Made (E-Jurnal Manajemen; Vol 2 No 9 (2013), 2013)
Humans have a variety of needs that must be met. Several methods are used to meet the needs of one way to shop. Advances in technology and the Internet affect the development of the type of retail business, the online store. To conduct online sales, businesses have to pay attention to the target market to be addressed, one of which is the demographic variables and technology readiness. This study aimed to determine the effect of demographic variables and the technology readiness of a person to the online shopping behavior. This study is located in the city of Denpasar, using as many as 100 respondents. Data collection methods used in this research is using questionnaires. The data analysis technique used is multiple linear regression analysis. This result proves that the technology readiness demographic variables and simultaneous significant effect on the behavior of online shopping in the city of Denpasar. In the partial test results shows demographic variables and a significant positive effect on online shopping behavior. Technology readiness partially positive and significant impact on online shopping behavior.
Keywords: Demographic variables, technology readiness, online shopping behavior.